Meta Consent – A Flexible Solution to the Problem of Secondary Use of Health Data. (15th September 2016) - Ploug, Thomas; Holm, Søren
Abstract: In this article we provide an in‐depth description of a new model of informed consent called 'meta consent' and consider its practical implementation. We explore justifications for preferring meta consent over alternative models of consent as a solution to the problem of secondary use of health data for research. We finally argue that meta consent strikes an appropriate balance between enabling valuable research and protecting the individual.